Enhancing coping skills through brief interventions during cancer therapy – a quasi-experimental clinical pilot study - Gelse, Norbert; Bodschwinna, Daniela; Jarczok, Marc N.; Wanner, Magdalena; Volz, Madeleine; Mayer-Steinacker, Regine; Huober, Jens; Gündel, Harald; Hönig, Klaus (Frontiers in Psychology, 2023)
Introduction Psycho-oncological interventions can reduce distress by activating individual resources and enhancing coping skills. Since medical cancer treatment is performed increasingly in outpatient settings, there is a growing need for evidence-based and brief interventions to be integrated seamlessly into these treatment procedures. The aim of the present pilot study is to examine the feasibility of brief interventions to cope with illness in this area. Methods A single center quasi-experimental design was developed in oncological outpatients at the University Medical Center Ulm, Germany, including N = 60 individuals with cancer undergoing chemotherapy or immunotherapy. The intervention group (IG) consisted of N = 40 participants. These were assigned to either cognitive behavioral interventions (CBI) or hypnotherapeutic interventions (HTI). The interventions each comprised three individual one-hour sessions. In addition, a waiting control group (WCG of N = 20) was set up, receiving care-as-usual. Primary outcomes were feasibility measures such as recruitment rates, participant retention rates, and complete data rates. Clinical results were discussed for the feasibility of a comprehensive efficacy study. Results The recruitment and completion rates illustrate demand and acceptance of the offer. Of the 208 individuals with cancer offered to participate in the study, 77 were interested in enrolling. This rate of 37% roughly corresponds to the use of psycho-oncological services in general. 17 individuals (22%) withdraw from participation before the intervention began due to severe deterioration in their disease. Once started, all 40 individuals of the IG (100%) completed the intervention, and 17 individuals of the WCG (85%) completed the accompanying questionnaires. Tentative results on clinical outcomes indicate that brief interventions on resource activation could have lasting effects on well-being and stress management. Discussion With this feasibility study, we aimed to explore the potential of brief interventions such as hypnotherapeutic and cognitive-behavioral approaches in psycho-oncology as an integral part of oncology day care. Even with a small number of participants results seem to indicate that the study design and brief interventions such as those presented can offer a low-threshold service that can be seamlessly integrated into oncological therapy. Given the promising results of this pilot study, we propose a full RCT on the effectiveness of such a brief intervention program. Clinical trial registration https://www.drks.de, German Trials Register (DRKS00019095).